Mesoporous Silica Nanoparticles Sebagai Drug Carrier pada Aplikasi Controlled Drug Delivery System - Ananda, Muhammad Bagas (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2020)
There are many DDS (Drug Delivery System) methods that can be used in this decade. The DDS method with nanotechnology is also increasingly in demand because it can be a controlled DDS (CDDS). One of the nanomaterials that can be useful for this purpose is Mesporous Silica Nanoparticle or MSN. This article provides a review that discusses how MSN can deliver drugs, the synthesis method and its level of ability in DDS. MSN showed that its ability to deliver various types of drugs including Ibuprofen, Doxorubicin and general antibiotics. The results of the synthesis can use solution based and EISA where the release properties in DDS are quite effective. This shows that MSN is good for the use of CDDS.